Characterization of Cenomanian-Turonian oxic facies in Tunisia: sequence stratigraphy and correlation of recorded bioevents - Hanini, Amine; Houla, Yassine; DJAIZ, Foued; Chairat, Imen; Mabrouk Boughdiri; Maamri, Ridha; Zagrarni,Mohamed-Faouzi (Arabian Journal of Geosciences, 2021)
On the southwestern Tethyan Margin of Tunisia, the well-known anoxic black shale facies of the Cenomanian-Turonian transition contrasts with oxic fossiliferous carbonates, first characterized here as lateral equivalents. In terms of sequence stratigraphy, the analysis of four wisely sampled sections in Central and Southern Tunisia led to interpret these deposits as a transgressive interval (TST). This interval spans the Whiteinella archaeocretacea Zone of foraminifera and is capped with a glauconite-rich highly bioturbated maximum flooding surface (MFS). In the reference section of Oued Bahloul and the Kalaat Senan area of North-Central Tunisia, these deposits overlay a Shelf Margin Wedge made of conglomeratic and bioclastic limestones. In South-Central and Southern Tunisia, the TST is characterized by the onset of oxic facies relaying laminated carbonates with local emergence surfaces. The analysis of both oxic and anoxic facies from the Cenomanian-Turonian transition allows identifying five successive bioevent markers, known elsewhere within the Tethyan domain: the extinction of the foraminifera genus Rotalipora (or Thomasinella), the Heterohelix shift, the Whiteinella proliferation, the filament event, and the appearance of Helvetotruncana helvetica. Among these bioevents, the Heterohelix shift coincides with the transgressive surface, while the filament event announces the maximal flooding surface. These Cenomanian-Turonian transition bioevents are of a particular relevance for regional and long-distance high-resolution correlations.